2021
DOI: 10.4103/jpgm.jpgm_1027_20
|View full text |Cite
|
Sign up to set email alerts
|

Severe myocardial bridge presenting as paroxysmal atrioventricular block

Abstract: Chest pain complicated with electrocardiographic changes is not an uncommon scenario in emergency departments, which should be examined cautiously. We describe a 51-years-old man with a myocardial bridge of coronary artery presenting with simultaneous Mobitz type I atrioventricular block on electrocardiography. Echocardiography excluded valvular abnormality and systolic/diastolic dysfunction. Coronary angiography confirmed the diagnosis of a myocardial bridge at the middle segment of the left anterior descendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Electrocardiographic changes are frequent, but there are reported cases of pseudo-Wellens’ (biphasic T-waves or deep T-wave inversions in leads V2 and V3), VF, transient STE, and atrioventricular block [ 9 , 11 , 16 , 17 ]. Echocardiographic findings have revealed an abnormal left ventricular strain pattern, diastolic dysfunction, myocardial stunning, and SRC.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiographic changes are frequent, but there are reported cases of pseudo-Wellens’ (biphasic T-waves or deep T-wave inversions in leads V2 and V3), VF, transient STE, and atrioventricular block [ 9 , 11 , 16 , 17 ]. Echocardiographic findings have revealed an abnormal left ventricular strain pattern, diastolic dysfunction, myocardial stunning, and SRC.…”
Section: Discussionmentioning
confidence: 99%
“…Though any coronary artery can be involved in MB, the studies showed that the left anterior descending artery is most commonly involved in MB. In contrast, the left circumflex and right coronary arteries are rarely affected [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 The rare presentation of coronary artery aneurysm combined with myocardial bridge was also reported by Ye et al 10 In addition, MB was reported with atrioventricular block which is a potential cause of repeated myocardial infarction and conduction abnormality. 8 MB has mostly been reported at autopsy. MB-induced myocardial ischemia has rarely been reported in a live individual.…”
Section: Discussionmentioning
confidence: 99%